Membrane barriers for guided bone regeneration: An overview of available biomaterials - Mizraji, Gabriel; Davidzohn, Alon; Gursoy, Mervi; Gursoy, Ulvi; Shapira, Lior; Wilensky, Asaf (Periodontology 2000, 2023)
Dental implants revolutionized the treatment options for restoring form, function, and esthetics when one or more teeth are missing. At sites of insufficient bone, guided bone regeneration (GBR) is performed either prior to or in conjunction with implant placement to achieve a three‐dimensional prosthetic‐driven implant position. To date, GBR is well documented, widely used, and constitutes a predictable and successful approach for lateral and vertical bone augmentation of atrophic ridges. Evidence suggests that the use of barrier membranes maintains the major biological principles of GBR. Since the material used to construct barrier membranes ultimately dictates its characteristics and its ability to maintain the biological principles of GBR, several materials have been used over time. This review, summarizes the evolution of barrier membranes, focusing on the characteristics, advantages, and disadvantages of available occlusive barrier membranes and presents results of updated meta‐analyses focusing on the effects of these membranes on the overall outcome.